As lógicas agroextrativistas e os projetos de desenvolvimento agrícola nas Ilhas do Capim, Caripetuba e Xingu em Abaetetuba - Pará - FELIZARDO, Alciene Oliveira (Universidade Federal do Pará, 2019)
The study of expansion mid-organic amazonic is a challenge, in the metmatization of specfies of biological and fisical space, human specifies and productions logicals in this territory. This work examines how the productive logical of agroextrativistas influenced the process of technological innovation triggered by the agricultural development projects implemented in the Capim, Caripetuba and Xingu’s islands in Abaetetuba, Pará. To meet this purpose, the reflections articulates the theoretical-analytical resources related to three central themes, productive arrays that guide the development projects in rural areas, the process of introducing technological innovations from agricultural development projects and the systemic approach applied to the study of the productive strategies. This work chose to analyze the "Project Producing the Inclusion" implemented by the Association of Residents of the Abaetetuba’s islands. It has been found that the productive logic of agroextrativistas families have been decisive in the process of technological innovation triggered by the agricultural development projects on the islands of Abaetetuba. This occurs in function of the decision-making centers develop their specific strategies based on the endogeneity of the practices carried out in their family farms. The complexity of logics of the agroextrativistas identified, reveals the need for a change of focus in the processes of interventions designed to realities such as the Capim, Caripetuba and Xingu’s islands, related in the Amazon territory. The programmatic approach, used by the "Project Producing the Inclusion" caused the nonpermanence of technological innovation in the systems family establishment. In addition, there is a need for advances in interventions that enable the strengthening of animal husbandry based on strategic approach adopted by agroextrativistas.